Test With Oral Administration of Clomiphene May Add to Differential Diagnosis of Severe Hyperandrogenism in Postmenopausal Women - A Case Report - Sartori, Yasmin Rodrigues de Camargo; Martins, Elaise Gabriele; Sebastianes, Fernando Moreno (Brazilian Journal of Case Reports, 2024)
A 62-year-old female patient, in menopause since the age of 47, presented with severe and virilizing hyperandrogenism condition that had been progressing for 10 years, with plasma testosterone levels above 500 ng/dL. Medical history included Cushing ’s disease in remission since hypophysectomy in 2014 and obesity. On imaging tests, there was an adenoma in the left adrenal gland with normal ovaries. Serum DHEA-sulfate concentrations, however, were normal and pelvic ultrasound and magnetic resonance imaging showed no ovarian lesions. Given the etiological doubt of hyperandrogenism, ovarian or adrenal, an additional test was necessary. However, serum gonadotropin concentrations were low, preventing testing with a GnRH analogue. A test was carried out with Clomiphene - a selective estrogen receptor modulator that stimulates the secretion of gonadotropins - at a dose of 50 mg/day orally for 5 days. Serum testosterone concentrations increased from 670 ng/dL, pre-use, to 893 ng/dL post-use, suggesting ovarian origin. The patient underwent bilateral oophorectomy and a Leydig cell tumor was confirmed. Therefore, we suggest that in women with hyperandrogenism of undefined origin, with suppressed concentrations of plasma gonadotropins, a clomiphene administration test be performed. The significant increase in plasma testosterone concentrations is indicative of the ovarian origin of the condition.